(untitled) (Iraqi Journal of Medical Sciences, 2024)
Background: Urinary tract infection (UTI) is the leading cause of bacteremia in hospitalized patients and the most prevalent nosocomial infection, making up as much as 35% of all infections in healthcare facilities. Clinical microbiology labs deal with many cases of UTI, and the most common cause of UTI is still enteric bacteria, namely Escherichia coli (E. coli). Objective: To isolate and identify E. coli in urine and determine their connection to antibiotic resistance. Methods: A consultant doctor from many hospitals oversaw the patients and a nurse was collected of 100 urine samples from patients suffering from UTI. Due to the large number of E. coli isolates (50 in total) and the use of polymerase chain reaction (PCR) technology for molecular detection of the diagnostic element 16SrRNA, the conventional techniques of bacterial identification were verified before PCR. Results: A total of 50 (50%) of the bacterial isolates were determined to be E. coli after culturing, biochemical, and molecular testing. E. coli was shown to be multidrug resistant (MDR) after an antibiotic susceptibility test. Assessment of antibiotic resistance was done on 25 isolates, and revealed that one (4%) is resistant to Nitrofurantoin, seven (28%) to Gentamicin, fifteen (60%) to Ciprofloxacin, and sixteen (64%) to Tetracycline. A total of 24 (96%) bacterial isolates are Carbenicillin-resistant; 18 (72%) of these isolates are resistant to Novobiocin, 20 (80%) to Cefotaxime, 22 (88%) to Ceftazidime, 23 (92%) to Rifampin, and 24 (96%) to Carbenicillin. Based on PCR results, all E. coli bacteria had the diagnostic gene 16SrRNA. Conclusion: This study found that nitrofurantoin is the antibiotic of choice for treating E. coli UTI, and the 16SrRNA gene is a confirmative diagnostic gene for E. coli infection. Keywords: E. coli, antibiotics, multidrug resistance, 16SrRNA Citation: Abbood SA. Isolation and molecular identification of multidrug resistance Escherichia coli isolated from patients with urinary tract infections. Iraqi JMS. 2024; 22(1): 36-44. doi: 10.22578/IJMS.22.1.5